2021
DOI: 10.22146/ijc.56587
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of a Kinetically Stable Topical Nanoemulsion Containing the Whitening Agent Kojic Acid

Abstract: The research was carried out to synthesize a stable kojic acid (KA) encapsulated nanoemulsion as a whitening agent for topical skin usage. In this study, the oil-in-water (O/W) KA nanoemulsion was formulated using integrated low and high energy methods that combined ultrasonic and hot temperature inversion methods. Several different combinations of parameters were screened, viz. xanthan gum amount (1.0 to 2.0 g), kojic acid (KA) amount (0.5 to 1.5 g), and surfactant-to-water ratio (1:10.75 to 1:4.875), to prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The highest ratio of Tween 80 to water (1:4.875 v/v) produced the best PDI of 0.255 ± 0.006, corresponding to an average particle size of 90.57 1.401 nm, according to the study. The absence of phase separation nanoemulsion indicated good storage capability at low temperature (2°C) and room temperature (25°C) 48 . Ilke Kildaci, et al prepared and characterized Linum usitatissimum nanoemulsion for treating atopic dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…The highest ratio of Tween 80 to water (1:4.875 v/v) produced the best PDI of 0.255 ± 0.006, corresponding to an average particle size of 90.57 1.401 nm, according to the study. The absence of phase separation nanoemulsion indicated good storage capability at low temperature (2°C) and room temperature (25°C) 48 . Ilke Kildaci, et al prepared and characterized Linum usitatissimum nanoemulsion for treating atopic dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…A very recent study on different formulations of oil-in-water (O/W) kojic acid nanoemulsion for topical application [100]. The study revealed various parameters to generate kinetically stable nanoemulsion at a recommended pH range of pH 4.95 to 5.18 for 6 weeks storage.…”
Section: Studies On Azelaic Acid-loaded Nanoparticlesmentioning
confidence: 99%
“…9 KA is inherently a hydrophilic drug, in contrast, hydrophobic active agents tend to absorb better into the stratum corneum, which poses a challenge in KA formulation. 9,10 This emphasizes the importance of using emulgel as a suitable vehicle for the penetration of KA over the stratum corneum of the skin. 11,12 Emulgels represent oil-in-water or water-in-oil emulsions that solidify through the addition of a gelling agent.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, encapsulating KA within emulgel not bolsters the physicochemical stability of the system, preventing drug exposure into unwanted storage condition. 9,10 This encapsulation approach amplifies the delivery of the active ingredient by surmounting diffusion challenges posed by the stratum corneum barrier, ultimately ensuring a higher concentration of the active ingredient reaching the target area. 9 The adhesive properties of emulgel extend the contact period of the drug on the skin, enhancing its efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation